A Review of Roles of Uterine Artery Doppler in Pregnancy Complications - Tian, Yingying; Yang, Xiuhua (Frontiers in Medicine, 2022)
The invasion of trophoblasts into the uterine decidua and decidual vessels is critical for the formation of placenta. The defects of placentation are related to the etiologies of preeclampsia (PE), fetal growth restriction (FGR), and small-for-gestational age (SGA) neonates. It is possible to predict significant vascular events during pregnancy through uterine artery Doppler (UAD). From the implantation stage to the end of pregnancy, detecting changes in uterine and placental blood vessels can provide a favorable diagnostic instrument for pregnancy complications. This review aims to collect literature about the roles of UAD in pregnancy complications. We consider all relevant articles in English from January 1, 1983 to October 30, 2021. Predicting pregnancy complications in advance allows practitioners to prevent and carry out timely interventions to avoid or lessen the harm to mothers and neonates. Administering low-dose aspirin daily before 16 weeks of pregnancy can significantly reduce the incidence of pregnancy complications. From early pregnancy to late pregnancy, UAD can combine with other maternal factors, biochemical indicators, and fetal measurement data to identify high-risk population. The identification of high-risk groups can also lessen maternal mortality. Besides, through moderate risk stratification, stringent monitoring for high-risk pregnant women can be implemented, decreasing the incidence of adversities.